User Perceptions of Digital Public Service Quality: Sentiment Analysis of the MyPertamina Application Using Stochastic Gradient Descent - Sholeh, Moch. Badrus; Hakim, Faris Abdi El; Zawawi, Ahmad Abdullah; Museyibzada, Rabiyya (International Journal Administration, Business & Organization, 2026)
Digital public service applications are increasingly used to support the distribution of subsidized services and improve administrative efficiency. However, user perceptions of system reliability, transaction processes, and data verification procedures remain critical factors influencing service acceptance. This study aims to analyze public sentiment toward the quality of a digital public service application by examining user reviews and identifying dominant service issues affecting user experience. A quantitative approach was applied using user review data collected from the Google Play Store. The textual data were processed through several stages of preprocessing and then classified into positive, neutral, and negative sentiments using the Stochastic Gradient Descent algorithm. In addition, aspect based analysis was conducted to examine issues related to system reliability, transaction processes, and data management and verification. The results show that system reliability and application stability, particularly login processes, verification mechanisms, and system updates, are the most influential factors shaping user sentiment. Transaction related issues such as payment failures and barcode scanning problems also contribute to negative perceptions, although some users acknowledge the convenience and speed of digital transactions. The study concludes that improving system stability and simplifying verification procedures are essential to enhance user satisfaction and strengthen the effectiveness of digital public service implementation.